PENGARUH RETURN ON ASSET (ROA) CURRENT RATIO (CR) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PT MAYORA INDAH TBK PERIODE 2013-2022 - Aldi Pariawan; Yulian Bayu Ganar (Jurnal Sinergi Manajemen, 2024)
ABSTRACT This study aims to determine the effect of Return On Asset (ROA) Current Ratio (CR) and Earning Per Share (EPS) on the share price of PT Mayora Indah Tbk for the period 2013-2022. This research uses Descriptive Quantitative methods with hypothesis testing. This research used descriptive statistical tests, classical assumption tests, multiple linear regression tests, hypothesis tests (t tests and f tests), and coefficient of determination tests with the help of the SPSS (Statistical Product Service Solution) program version 26. Based on the hypothesis test perisal Effect of Return On Asset (X1) show sthat t count < t table where 1.016 < 2.364 and a significant value of 0.349 > 0.05, so that Return On Asset has no effect and is not significant to the stock price.T heresults of hypothesis testing in terms of the effect of Current Ratio (X2) show that tcount < t table where 1,260 < 2,364 and a significant value of 0.255> 0.05, so that Current Ratio has no effect and is not significant to stock prices.The results of hypothesis testing in terms of the effect of Earning Per Share (X3) show that t count > T table where-2.752 > 2.364 and a significant value of 0.03 < 0.05 so that Earning Per Share has a negative and significant effecton Stock Price.The test results simultan eously show that f count > f table where 5.343 > 4,35 with asignificant 0.039 < 0.05. so it can be concluded that Return On Asset, Current Ratio, and Earning Per Share havea significant effect on Price. Keywords: ROA, CR, EPS and stock Price.